Containers Push Toward the Mayfly Server. - Edwards, Chris (Communications of the ACM, 2016)
The article discusses the significance of the development of containers in computer operating systems, particularly concerning multitasking systems. It discusses the concept of virtualization and virtual machines (VMs), the efficiency of containers, and the creation and deletion of unikernal-based systems.